Exposure to nitrate from drinking water and the risk of childhood cancer in Denmark. (October 2021) - Stayner, Leslie T.; Schullehner, Jörg; Semark, Birgitte Dige; Jensen, Anja Søndergaard; Trabjerg, Betina B.; Pedersen, Marie; Olsen, Jørn; Hansen, Birgitte; Ward, Mary H.; Jones, Rena R.; Coffman, Vanessa R.; Pedersen, Carsten B.; et al.
Highlights: Nitrate is one of the most common pollutants found in drinking water worldwide. Our study included over one million births with individual level estimates of nitrate. We observed an association between nitrate and childhood nervous system cancers. We did not observe an association between nitrate and other childhood cancers. Current EU and US standards for nitrate in drinking water may not be adequate. Abstract: Background: There is limited evidence that nitrate, a common contaminant in drinking water, increases the risk of childhood cancers. Our objective was to examine this association in Denmark. Methods: We conducted a nationwide case-control study based on all singletons liveborn to Danish-born parents from 1991 to 2015 (N = 1, 219, 140) that included 596 leukemias, 180 lymphomas, and 310 central nervous system cancers (CNC) who were ≤15 years of age at diagnosis and were identified from the Danish Cancer Registry. Approximately 100 controls were randomly selected and matched to each case on date of birth and sex. Nitrate measurements in public water systems were linked with an address registry to estimate individual average nitrate concentrations during preconception, prenatal, and postnatal periods. Odd ratios (OR) and 95% confidence intervals (95%CI) were estimated using conditional logistic regression controlling for the matching variables, and birth order, birthweight, urbanicity, maternal education, employment, income and smoking, and parental age. Results: There was no evidence of an association of nitrate with leukemia or lymphoma. An association between CNC and the highest category of nitrate exposure (>25 mg/L nitrate) was observed for preconception (OR = 1.82, 95%CI:1.09 to 3.04), prenatal (OR = 1.65, 95%CI:0.97 to 2.81), and postnatal exposure (OR = 1.48, 95%CI:0.82 to 2.68) in fully adjusted models. There was also some evidence of an exposure–response in models of continuous nitrate exposure and CNC. Conclusions: Our findings provide some evidence that exposure to nitrate from drinking water may increase the risk of childhood CNC cancer, but not leukemia or lymphoma.